Effects of Multi Strain Probiotics on Egg Production and Quality in Laying Hens Fed Diets Containing Food Waste Product - Chung, Sung Heon; Lee, Jinyoung; Kong , Changsu (International Journal of Poultry Science, 2014)
The objective of the present study was to evaluate the effects of multistrain probiotics (MP) supplementation to diets containing 40% food waste product (FWP) on egg production and quality. Forty wk-old Lohmann Brown were allocated to 4 dietary treatments with 5 replicates and 2 birds/cage in completely randomized design. A basal diet formulated to contain corn, soybean meal and FWP and 3 additional diets were prepared by adding 0.1, 0.2, or 0.4% of MP. During the 3-wk feeding period, the addition of 0.4% MP showed the least egg production (75.4%) compared with 0 (85.5%) or 0.2% (81.4%) MP addition (p